2022
DOI: 10.3390/en15103774
|View full text |Cite
|
Sign up to set email alerts
|

Choice of the Arch Yielding Support for the Preparatory Roadway Located near the Fault

Abstract: The article presents a method of selecting an arch yielding support for preparatory workings driven in a hard coal seam. Particular attention was paid to discontinuous deformation in the form of a fault, which significantly contributes to the change of the excavation protection schemes. On the basis of the geometry of the machines and devices in the designed excavation, the support was selected, which was then checked for the ventilation criterion. In the next stage, analytical calculations were carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In order to explore the strain field evolution law of an anchored bedding rock mass under impact dynamic load, and to study the shear displacement process of a rock mass along the bedding direction, an ultrahigh-speed camera and digital speckle measurement technology were used during the test [ 33 , 39 ]. By capturing the y-direction strain cloud map of the dynamic load response of the anchored bedding rock mass from prepeak to postpeak under dynamic load, the strain field evolution law of anchored bedding rock mass was obtained.…”
Section: Test Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore the strain field evolution law of an anchored bedding rock mass under impact dynamic load, and to study the shear displacement process of a rock mass along the bedding direction, an ultrahigh-speed camera and digital speckle measurement technology were used during the test [ 33 , 39 ]. By capturing the y-direction strain cloud map of the dynamic load response of the anchored bedding rock mass from prepeak to postpeak under dynamic load, the strain field evolution law of anchored bedding rock mass was obtained.…”
Section: Test Results Analysismentioning
confidence: 99%
“…Wang Aiwen et al [ 32 ] found that there is an obvious time difference effect between the vibration of the bolt and the surrounding rock under impact loads, which leads to the asynchronous vibration of the bolt and the surrounding rock, resulting in the dynamic shear of the anchorage agent. Qiu Penggqi [ 33 ] believed that improving the antisliding characteristics and coordinated deformation ability of a rock, the anchoring agent and bolt can effectively prolong the anti-impact aging time of anchoring rock and reduce the impact of dynamic load on the supporting structure of surrounding anchoring rock. Skrzypkowski K [ 34 , 35 ] believed that the places of particular exposure to shear stresses are faults and layered roof layers; between them, there are surfaces of reduced cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, different countries have constructed corresponding systems for the prevention and control of rock burst based on their actual mining conditions [5][6][7]. A large number of scholars have conducted relevant research on the impact problem caused by underground excavation; for example, Mazaira et al [8] introduced the impact of rock bursts in underground excavation and related prevention and control measures; Askaripour, M. et al [9] studied the mechanism, types, and corresponding prediction methods of rock bursts in tunnel excavation; Skrzypkowski, K. et al [10] studied the correlation between the magnitude of dynamic loads from seismic sources on roadways and their propagation distance; Farhadian, H. [11] proposed the TCR classification method through the analysis of over 200 cases; Pan, J. et al [12] conducted a study on the rock burst mechanism considering the time-varying characteristics of coal seam main roadways, and developed a weakening and unloading plan primarily based on roof hydraulic fracturing; Wang, G. et al [13] constructed a mechanical model for the instability and failure of roadways based on the stress distribution characteristics of coal, explaining the mechanism behind the overall instability and failure of coal pillars; Gao, M. et al [14] proposed a fully anchored support technology by analyzing the main controlling factors of main roadway roof impact failure; Xia, Y. et al [15] identified the mechanism of repeated impact in main roadway groups in complex structural areas through factor analysis, and formulated targeted prevention methods by mainly utilizing roof super-long-hole horizontal segmented fracturing; Liu, S. et al [16] studied the mechanism of rock burst in the roadway region under working face mining influence, determining that preventing main roadway shock damage lies primarily in adjusting the width of coal pillars; Zheng, J. et al [17] considered the role played by hard roofs in causing roadway impact damage and proposed a method to weaken roof bands; Smoli ński, A. and Seryakov, V. M. et al [18,19] studied the stress state of the roof and the potential stress concentration of the roof under support. The above-mentioned studies all indicate that the mechanism of rock burst in coal seam main roadways is complex and significantly influenced by geological and mining technical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are key factors in determining the efficiency of roadway excavation and enterprise production efficiency. Skrzypkowski et al (2022) established a rock mass model with faults through RS3 numerical simulation software of finite element method, studied the displacement of steel frame support in areas with faults, and proposed the method of selecting arch compression support in the preparation work of hard coal seam excavation. Lawrence (2009) proposed a longwall roadway roof support model (GRSM) aiming at roadway development and mining area through the combination of numerical simulation and experience.…”
Section: Introductionmentioning
confidence: 99%